The timelines for the price and reimbursement authorization in Italy 2018–2020 - Gallo, Valentina; Alessi, Eva; Montilla, Simona; Altamura, Gianluca; Traversa, Giuseppe; Trotta, Francesco (Frontiers in Medicine, 2022)
Objective This investigation aimed to guarantee the principles of transparency in public administration; to inform citizens about the time to patient access to reimbursed medicines; to assess the duration of the P&R process for the first time in the period 2018–2020; and to evaluate whether and how the SARS-CoV-2 (COVID-19) pandemic affected the P&R activity. This study analyzed the timelines of pricing and reimbursement procedures submitted in Italy by the pharmaceutical marketing authorization holder (MAH) from 2018 to 2020. Methods The analysis was run through an AIFA web-based platform that collects data about P&R procedures for each step of the Italian Price and Reimbursement (P&R) procedure, including dates of the Technical Scientific Committee (CTS) and Price and Reimbursement Committee (CPR) meetings from January 2018 to December 2020. On this basis, four indicators were developed relating to the completion time of each stage of the P&R negotiation process and were defined in terms of days. In this regard, descriptive analyses, graphical boxplots, and survival curves (Kaplan–Meier) were carried out, studying these indicators in relation to the typology of pharmaceutical procedures. Results Overall, in the period 2018–2020, 57.1% of the 2,445 procedures entered were represented by the Off-patent pharmaceuticals procedures (generics, biosimilars, copies, and/or parallel trade). In 2020, the overall process duration for Off-patent pharmaceuticals procedures was equal to 129.8 average days [95% CI: (122.3–137.2)], with a median value of 108.0, whereas for In-patent pharmaceuticals procedures, it was equal to 283.1 average days [95% CI: (267.8–298.5)], with a median value of 284.0. Over time, the trend of the entire duration of the P&R process tended to decrease. In terms of estimated timing for the conclusion of each stage of the P&R negotiation process, the difference between Off-patent and In-patent pharmaceutical procedures was statistically significant by the Log-Rank test. Discussion and conclusion This is the first study to examine the time of the P&R process in Italy, from MAH submission to the publication of the final decision in the Italian Official Journal. The time span considered is 3 years, including the first year of the COVID-19 pandemic. Compared to European average times, in Italy, the time necessary for evaluation, authorization for reimbursement, and definition of the price of a medicine can be considered satisfactory.